Ação afirmativa : o impacto da política de cotas na ESDI (Escola Superior de Desenho Industrial - UERJ) - Sacramento, Mônica Pereira do (2008)
The current paper will focus on the impact of the racial and social quota system on senior black students from the competitive entrance exam (Vestibular) of ESDI (Superior School of Design) over the academic years 2003-2004, as well as on this school institution itself, where the presence of black students used to be nearly negligible before the implementation of an affirmative action law by the Brazilian government. Through empirical research, quantitative and qualitative interpretation of all collected data about this pioneering experience in the Brazilian Higher Education Institution system, the current study aims at portraying these young students, as well as determining the motivations that led them to choose a career in design, a highly respected university branch, which was almost limited to people from a wealthy background until few years ago. What kind of experience did these black and biracial students have upon entering a public university? How do they evaluate affirmative action policies? Which is the impact of university life on their own lives? How did the university institution change after the implementation of an affirmative action law? Upon entering this Higher Education school black students show an increasing range of expectations towards their own career and future opportunities and report their own strategies for studying and continuing within the academic institution.